Analysis of Hematological Examination Results in Pulmonary Tuberculosis (TB) Patients Undergoing Intensive Phase Anti-Tuberculosis Drug Therapy - Tanjung, Asbar (Jurnal Ilmiah Kesehatan, 2024)
The intensive phase of anti-tuberculosis (TB) drug therapy consists of a combination of antibiotics, including Isoniazid (INH), Rifampicin (RIF), Pyrazinamide (PZA), and Ethambutol (EMB). The primary goal of this therapy is to inhibit the growth and spread of Mycobacterium tuberculosis, preventing its migration from the lungs to other organs. However, intensive-phase therapy may result in both major and minor side effects. This study aims to analyze the hematological profiles of pulmonary TB patients undergoing intensive-phase anti-tuberculosis treatment. The respondents were pulmonary TB patients recruited from primary healthcare centers within the East Bekasi District, Bekasi City. Those who met the sample criteria underwent hematological examinations, including hemoglobin (Hb), hematocrit (HCT), red blood cell count, white blood cell count, and platelet count. The tests were conducted using the electrical impedance method with a hematology analyzer. The hematological examination revealed a trend of low hemoglobin levels, with the average Hb recorded at 11.98 ± 8.65 g/dL. Additionally, abnormal blood parameters were observed, with 33.3% of patients experiencing erythropenia, 57% showing thrombocytopenia, 33% presenting leukopenia, and 20% exhibiting leukocytosis. These findings confirm that intensive- phase anti-tuberculosis therapy affects the hematological profiles of pulmonary TB patients, highlighting the need for close monitoring during treatment.